MODEL KERAGAAN SAYUR DAN BUAH SEBELUM DAN SESUDAH ERUPSI GUNUNG SINABUNG DI KABUPATEN KARO SUMATERA UTARA - Satia Negara Lubis; T Sabrina; Lili Fauziah (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2016)
An eruption of Mount Sinabung since 2010 up to now have an impact on the production and export of vegetables and fruits in the district of Karo. The purpose of this research is 1) To analyze the supply-demand of vegetables and fruits in North Sumatra after the eruption of Mount Sinabung since 2010 and compare it with before the the eruption of Mount Sinabung And 2) To build a horticultural development model after the eruption of Mount Sinabung from the aspects of farming, middle-farm and post-harvest also policy simulation The analyzed data was the data series of Karo regency using the simultane model with method estimation two SLS. The result of analysis showed that there was no significant difference in the production of vegetables and fruits before and after the eruption of Mount Sinabung in Karo regency. While at the variable price shows that there was a significant difference before and after the eruption of Mount Sinabung As the simultaneous production, consumption, exports, domestic prices, horticulture export prices in the Karo district affect one another and the policy to develop production and horticulture export was by minimizing Bank Indonesia’s rate and decreasing the price of fertilizer by 10 percent.